Jawabanmu

2014-02-26T16:36:11+07:00
a. memfaktorkan
x²  -  x  -  6  = 0

(x-3) (x+2)    = 0
x-3 = 0    ∨    x+2 =0
x = 3              x = -2

b. kuadrat sempurna
x²  -  x  -  6  =  0
x²  -  x  =  6
(x - 1/2)² - (1/2)² = 6
(x - 1/2)² - 1/4 = 6
(x - 1/2)² = 6 + 1/4
x - 1/2 = √25/4
x - 1/2 = 5/2
x = 1/2 + 5/2 = 6/2 = 3                    x = 1/2 - 5/2 = - 4/2 = -2

c. rumus ABC

X = -(-1)   √(-1)² - 4(1)(-6) / 2(1)
   = 1 √1 - (-24) / 2
   = 1 √1+24 / 2
   = 1 √25 /2
   = 1 5 /2
x = 1+5 / 2 = 6/2 = 3                         x = 1-5 / 2 = -4/2 = -2










ini bnr ga
insyaallah bener ... kamu bisa cek sendiri ko
mksh yya :)
iya sama sama :)